The Wei Lang's Sutra through the Perspectives of Theravada Buddhism - Homdok, Phra Kittipong; Taileelais, Phra Kamolrat; Peykaeo, Phramaha Rangsey; Pandee, Phromphong (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This academic paper aims to study the Wei Lang's Sutra through the perspectives of theravada buddhism. There are the 3 objectives; 1) To study the concept of Wei Lang's Sutra 2) To study the similarity of concept with theravada buddhism 3) To apply the dharma principles in daily life. The Wei Lang's Sutra is essence by using the wisdom to find the path obtain to buddhahood and for liberation from all the defilements of this world. The similarity with theravada buddhism is the main core matched to the dependent origination (Paticca-Samuppada) and the four noble truths. The application of dharma principles must be understood by practitioners accordingly and they are necessary often practiced.